(3TQM bUjOg CHj Ydi Hf GdgjKe GdHZOGOis - (3eMeO Hf CMeO Hf gTGe Hf Nda GddNej GdCfOdSj, CHh YHO Gddg,J (B577 (3g` s; (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3SCdJfi habfi Gddg hEjGc dEQGOJg Cf TQM dc gPg GdbUjOg TQMkG TGajkG s
(3BNQgG (B:s
(3aQGOi LeY aQO heKfi eYOhd Yf GKfjf jbGd TaYJ GdhJQ EPG UjQJg RhLkG jYfi Cf Gddg hGMO djS jTaY Cj jLYd eYg KGf dG Edg ZjQg s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
Keywords: (3Gdadcs